A preparation method for improving the suspension stability of selenium disulfide lotion

CN122937091APending Publication Date: 2026-10-20大有药业扬州有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611406620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]为了解决因相关技术采用增稠剂而导致难以兼顾沉降抑制、含量均匀与流动恢复性能的问题,本申请提供一种提高二硫化硒洗剂悬浮稳定性的制备方法

Benefits of technology

1、本申请采用糖醇与螯合剂预先构建抗氧化连续相,再将二硫化硒预分散、湿法分散形成窄粒径分散相,随后与纤维素醚和黄原胶构成的结构相混合,其中糖醇同步提高了连续相密度与黏度、缩小了颗粒与连续相的有效密度差,螯合剂降低了金属离子对颗粒表面氧化的催化作用,纤维素醚与黄原胶则形成了可剪切恢复的弱凝胶网络,获得了二硫化硒洗剂在长期静置条件下沉降缓慢、不易分层、含量均匀且可恢复流动的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the fields of pharmaceutical formulations and daily chemical products, specifically disclosing a method for preparing a selenium sulfide lotion with improved suspension stability. The method includes the following steps: S1, mixing and dissolving purified water, sugar alcohol, and a chelating agent to obtain an antioxidant continuous phase; S2, adding selenium sulfide raw material to the antioxidant continuous phase and pre-dispersing it to obtain a selenium sulfide premix; S3, adding a wetting and dispersing agent to the selenium sulfide premix and performing wet dispersion treatment; S4, dispersing cellulose ether and xanthan gum separately in the aqueous phase to obtain a structural phase; S5, mixing the narrow-particle-size selenium sulfide dispersed phase and the structural phase, and performing dispersion and homogenization treatment; S6, allowing the initial selenium sulfide lotion product to stand for equilibrium to obtain the selenium sulfide lotion. The selenium sulfide lotion of this application is used as a topical lotion for dandruff removal, antifungal purposes, and inhibiting sebum secretion. It has the advantages of slow sedimentation under long-term static conditions, resistance to stratification, uniform content, and the ability to restore flow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the fields of pharmaceutical formulations and daily chemical products, and more specifically, it relates to a method for preparing a selenium disulfide detergent with improved suspension stability. Background Technology

[0002] In the fields of pharmaceuticals and daily chemical detergents, to improve the suspension stability of heavy particles such as selenium disulfide, existing technologies have adopted various methods to improve the suspension stability of heavy particles. These methods include introducing a single thickener or water-soluble polymer to construct a high-viscosity continuous phase to delay particle sedimentation, or refining active particles through mechanical grinding or ball milling to improve dispersion uniformity. Some solutions also employ a single antioxidant or inert atmosphere protection to inhibit the surface oxidation of selenium disulfide. These technologies can reduce the stratification rate, simplify the production process, or maintain short-term appearance uniformity to a certain extent in their respective application scenarios. Therefore, they are widely used in topical formulations and anti-dandruff detergents, constituting a mature technological accumulation for improving suspension stability in this field.

[0003] However, while related technologies rely on thickeners to increase the viscosity of the system and temporarily delay sedimentation, they often lead to loss of system fluidity and the formation of dense, hard precipitates that are difficult to redisperse after standing. Although refining the particle size can reduce the sedimentation rate of individual particles, it cannot suppress secondary agglomeration and flocculation between fine particles, and stratification and uneven content will still occur in the later stages of storage. Furthermore, if there is a lack of synergistic control against oxidation and discoloration while thickening, oxidation products will change the surface properties of particles and further aggravate agglomeration and sedimentation, making it difficult to simultaneously achieve sedimentation inhibition, content uniformity, and flow recovery performance. Summary of the Invention

[0004] To address the problem that the use of thickeners in related technologies makes it difficult to simultaneously achieve sedimentation inhibition, content uniformity, and flow recovery performance, this application provides a method for preparing selenium disulfide detergents with improved suspension stability.

[0005] This application provides a method for preparing a selenium disulfide detergent with improved suspension stability, using the following technical solution: A method for preparing a detergent with improved suspension stability includes the following steps: S1. Mix and dissolve purified water, sugar alcohol and chelating agent to obtain an antioxidant continuous phase; S2. Selenium disulfide raw material is added to the antioxidant continuous phase for pre-dispersion to obtain selenium disulfide premix; S3. Add a wetting and dispersing agent to the selenium disulfide premix and perform wet dispersion treatment to obtain a narrow particle size selenium disulfide dispersed phase. S4. Cellulose ether and xanthan gum are separately dispersed in an aqueous phase containing glycerol, and then mixed after swelling and hydration treatment to obtain the structural phase; S5. Mix the narrow-particle-size selenium disulfide dispersed phase with the structural phase, and perform dispersion and homogenization treatment to obtain the initial product of selenium disulfide detergent. S6. The initial product of selenium disulfide detergent is allowed to stand and balance to obtain a selenium disulfide detergent with improved suspension stability. Based on the total mass of the selenium disulfide detergent, the selenium disulfide content is 2.5% w / w, the sugar alcohol content is 2% to 6%, the chelating agent content is 0.05% to 0.15%, the cellulose ether content is 0.30% to 0.70%, the xanthan gum content is 0.05% to 0.20%, the mass ratio of the cellulose ether to the xanthan gum is 4:1 to 10:1, the external phase pH of the detergent is 3.0 to 4.0, and the balance is pure water.

[0006] By adopting the above technical solution, since the chelating agent and sugar alcohol are pre-dissolved in purified water to form a homogeneous continuous phase, the chelating agent preferentially combines with divalent metal ions in the system to reduce its catalytic effect on the subsequent oxidation of the selenium disulfide particle surface. The sugar alcohol simultaneously increases the density and viscosity of the continuous phase and reduces the effective density difference between the selenium disulfide particles and the continuous phase. Therefore, in the subsequent pre-dispersion and wet dispersion steps, the wetting, disintegration and dispersion of selenium disulfide particles are more uniform, and the gravity sedimentation driving force under static conditions is weakened in advance, laying the foundation for overall suspension stability.

[0007] Preferably, in step S1, the sugar alcohol is one or more of glycerol, sucrose, or sorbitol; the chelating agent is one or more of disodium ethylenediaminetetraacetate, sodium citrate, or sodium phytate; the mixing and dissolving temperature is 20°C to 30°C, the stirring rate is 100 r / min to 300 r / min, and the time is 10 min to 30 min.

[0008] By adopting the above technical solution, since glycerol, sucrose, or sorbitol are sugar alcohol components, their multiple hydroxyl groups can form hydrogen bonds with water molecules, thus gently increasing the viscosity and density of the continuous phase. Moreover, these substances are highly safe and compatible with the subsequent cellulose ether and xanthan gum networks. Using disodium EDTA, sodium citrate, or sodium phytate as chelating agents allows for flexible selection of chelation strength based on the ionic composition and pH conditions of the system. Stirring at a set temperature can ensure complete dissolution while avoiding premature introduction of bubbles or overheating. Therefore, the resulting antioxidant continuous phase components are evenly distributed and have moderate viscosity, serving as both a raw material dispersion medium for selenium disulfide and preventing the initial viscosity from being too high during subsequent structural phase mixing, which would affect network construction.

[0009] Preferably, before step S2, a pretreatment of the selenium disulfide raw material is included: the selenium disulfide raw material is dried at low temperature under an inert atmosphere, with a drying temperature of 30°C to 40°C, a vacuum degree of -0.08MPa to -0.10MPa, and a time of 2h to 4h; then the dried selenium disulfide raw material is sieved with a sieve mesh of 200 to 400 mesh, and the undersize material is collected as the selenium disulfide raw material used in step S2.

[0010] By adopting the above technical solution, the low-temperature vacuum drying under an inert atmosphere removes moisture from the selenium disulfide raw material while avoiding surface oxidation or crystal changes caused by high temperature and oxygen exposure. This keeps the surface of the raw material particles clean and active, which is conducive to the adsorption of subsequent wetting and dispersing agents. Sieving removes agglomerated large particles and mechanical impurities and controls the particle size of the raw material within a certain range. Therefore, the initial particle size distribution of the raw material entering S2 pre-dispersion is narrow and the moisture content is low, which provides a prerequisite for S3 to achieve the target particle size distribution and reduce over-grinding. It also reduces the risk of changing the viscosity and pH of the continuous phase due to the introduction of moisture from the raw material.

[0011] Preferably, in step S3, the wetting and dispersing agent is one or more of polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monolaurate, or cocamidopropyl betaine; based on the total mass of the selenium disulfide detergent, the content of the wetting and dispersing agent is 0.1% to 0.8%; the wet dispersion treatment adopts a rotor-stator dispersion method, the dispersion rate is 2000 r / min to 5000 r / min, the time is 5 min to 20 min, and the system temperature does not exceed 30℃ during the treatment; the dispersion is stopped after D50 reaches 3 μm to 8 μm and D90 ≤ 15 μm.

[0012] By adopting the above technical solution, the wetting and dispersing agent is directionally adsorbed on the surface of selenium disulfide particles to form a steric hindrance layer. The nonionic segments of polyoxyethylene sorbitan monooleate and polyoxyethylene sorbitan monolaurate provide steric stabilization. Cocamidopropyl betaine takes into account both wetting and dispersion and reduces foaming under mild conditions. Combined with the high shear effect of the rotor-stator dispersion mode, the particles are gradually deagglomerated rather than excessively broken. Therefore, the grinding is stopped in time after the particles reach the target particle size distribution. This reduces the settling velocity of individual particles and avoids secondary agglomeration caused by excessively fine particle size leading to excessive specific surface area and enhanced van der Waals attraction. At the same time, the temperature does not exceed 30°C throughout the process, which inhibits oxidation and network degradation induced by local overheating.

[0013] Preferably, after step S3, an antioxidant protection is further included: a reducing agent is added to the narrow-particle-size selenium disulfide dispersion, wherein the reducing agent is one or more of sodium metabisulfite, sodium bisulfite, or ascorbic acid, and the content is 0.05% to 0.30%; then a citric acid or citrate buffer system is added to adjust the pH of the system to 3.0 to 4.0 to obtain an antioxidant narrow-particle-size selenium disulfide dispersion for mixing in step S5.

[0014] By adopting the above technical solution, since the reducing agent preferentially consumes dissolved oxygen and initial oxidation products in the system to maintain the selenium disulfide surface in a reduced state, the order of adding chelating agent and reducing agent first and pH adjustment later allows the antioxidant components to be uniformly distributed on the particle surface first, and then the pH is locked at the set range by the citric acid or citrate buffer system. Therefore, the acidic environment not only inhibits metal catalytic oxidation itself, but also forms a synergistic antioxidant boundary with chelation and reduction, preventing oxidation products from changing the surface charge and adsorption behavior of selenium disulfide. This allows the resulting dispersed phase to maintain the particle dispersion state and network compatibility during subsequent mixing with the structural phase and long-term storage.

[0015] Preferably, in step S4, the mass ratio of cellulose ether to xanthan gum is 4:1 to 10:1; the swelling and hydration temperature of the cellulose ether is 20°C to 30°C, and the time is 30 min to 60 min; the dispersion temperature of the xanthan gum is 20°C to 30°C, the dispersion rate is 500 r / min to 1500 r / min, and the time is 10 min to 30 min; the mass ratio of glycerol to xanthan gum in the structural phase is 5:1 to 20:1.

[0016] By adopting the above technical solution, cellulose ether provides continuous viscoelastic support as the main network skeleton, while xanthan gum fills the network nodes in a lower amount to strengthen the low shear yield stress and endow the system with shear dilution and structural recovery capabilities. The two work together in a set mass ratio to form a recoverable weak gel without excessive thickening. Glycerol in the structural phase serves as both a hydration aid for xanthan gum dispersion and maintains consistency with the sugar alcohol component of the continuous phase through its hydroxyl groups. Therefore, the structural phase after sufficient swelling and hydration at the set temperature has a uniform, relaxed, and redispersible network, which reserves structural accommodation space for the mild mixing with the selenium disulfide dispersed phase in S5 and avoids premature network formation and high shear damage.

[0017] Preferably, in step S5, the mixing is as follows: the structural phase is slowly added to the narrow-particle-size selenium disulfide dispersion phase at a stirring rate of 1000 r / min to 2500 r / min for 10 min to 30 min, and then stirring is continued at 1000 r / min to 2500 r / min for 10 min to 30 min; the homogenization pressure of the homogenization treatment is 5 MPa to 20 MPa, the number of cycles is 1 to 3, and the system temperature does not exceed 35°C during the homogenization process.

[0018] By adopting the above technical solution, the weak gel network of the structural phase is gradually wrapped around the selenium disulfide particles stabilized by the wetting and dispersing agent during the formation process by slowly adding the structural phase to the dispersed phase and controlling the feeding and stirring rates. This avoids flocculation or network collapse caused by excessively high local concentrations. The subsequent low-pressure homogenization is only used to eliminate macroscopic inhomogeneities and trapped air bubbles without strengthening grinding. Therefore, the particles are uniformly anchored in the three-dimensional network and the network can recover after shearing. This achieves both the support of the particles when standing and the retention of the flow and redispersibility when tilting and gently shaking. The temperature does not exceed the set value throughout the process, thus protecting the antioxidant boundary and network integrity.

[0019] Preferably, in step S5, before mixing the structural phase with the narrow-particle-size selenium disulfide dispersion, a surfactant is added to the narrow-particle-size selenium disulfide dispersion; the surfactant is one or more of sodium dodecyl sulfate, sodium lauroyl sarcosinate, or cocamidopropyl betaine, and the content is 0.5% to 3.0%.

[0020] By adopting the above technical solution, since the surfactant is pre-adsorbed on the interface between the selenium disulfide particles and the continuous phase before mixing, sodium dodecyl sulfate and sodium lauroyl sarcosinate provide appropriate anionic surface activity to promote wetting and reduce interfacial tension, and cocamidopropyl betaine buffers the compression of the double layer by the electrolyte with its zwitterionic properties, the particle surface is covered by the interfacial active layer when the structural phase is added, which reduces the non-specific bridging flocculation between the particles and the polymer network, making the distribution of particles in the weak gel more uniform, and improving the spreadability and skin feel of the detergent during application and rinsing.

[0021] Preferably, in step S6, the static equilibration is performed by allowing the sample to stand at 20°C to 25°C for 12 to 24 hours under light-protected conditions.

[0022] By adopting the above technical solution, the polymer network can complete relaxation and recombination under the condition of being free from light and heat disturbance due to the static equilibrium of avoiding light and constant temperature. The trapped micro bubbles can slowly escape, and the interaction between the adsorption layer on the particle surface and the continuous phase reaches quasi-equilibrium. Therefore, the viscosity, yield stress and particle distribution of the system tend to be stable. After standing, it is not easy for hard sediment to form at the bottom or for the clear liquid to separate from the upper layer to occur. This provides a structurally stable initial state for subsequent redispersion and long-term storage.

[0023] Preferably, in step S6, after the static equilibrium is completed, the selenium disulfide detergent is gently redispersed by turning it 5 to 20 times at a turning rate of 5 to 20 r / min for 1 to 5 min.

[0024] By adopting the above technical solution, the mild redispersion at a low tumbling rate allows the weak gel structure formed during standing to gradually disintegrate under low shear without destroying its three-dimensional topology. The particles are then redistributed uniformly in the network. Therefore, the macroscopic uniformity of the system is restored after a limited number of tumbling cycles. This avoids network breakage, secondary agglomeration of particles, or re-entry of bubbles caused by high shear redispersion, ensuring that the selenium disulfide content and dosage of the detergent remain consistent in the upper, middle, and lower layers.

[0025] In summary, this application has the following beneficial effects: 1. This application uses sugar alcohol and chelating agent to pre-construct an antioxidant continuous phase, and then pre-disperses and wet-disperses selenium disulfide to form a narrow particle size dispersed phase, which is then mixed with a structural phase composed of cellulose ether and xanthan gum. The sugar alcohol simultaneously increases the density and viscosity of the continuous phase and reduces the effective density difference between the particles and the continuous phase. The chelating agent reduces the catalytic effect of metal ions on the oxidation of the particle surface. The cellulose ether and xanthan gum form a shear-recoverable weak gel network, which achieves the effect of slow sedimentation, non-stratification, uniform content and recoverable flow of selenium disulfide detergent under long-term static conditions.

[0026] 2. In this application, the preferred method is to pretreat the selenium disulfide raw material by low-temperature drying and sieving under an inert atmosphere. After wet dispersion, a reducing agent and an acidic buffer system are added in sequence. Because the pretreatment makes the raw material surface clean, with low moisture content and narrow initial particle size distribution, the reducing agent maintains the particles in a reduced state, and the acidic environment and chelation effect form an antioxidant boundary, thereby achieving the effect of long-lasting particle dispersion, stable surface properties, and less oxidative discoloration and secondary agglomeration.

[0027] 3. In this application, wetting and dispersing agents are preferably used to form a steric hindrance layer by directional adsorption on the particle surface. The grinding is stopped in time after the particle size of the wet dispersion is controlled to a narrow distribution. Since nonionic and amphoteric dispersants take into account wetting, dispersion and foam suppression, the narrow particle size distribution reduces the settling velocity of single particles and avoids excessive agglomeration of fine particles. This results in the effect of uniform distribution of selenium disulfide particles in the continuous phase, no hard precipitate forming at the bottom and consistent content in the upper and lower layers.

[0028] 4. The method of this application involves slowly adding the structural phase to the dispersed phase while controlling the feeding and stirring rates, followed by low-pressure homogenization to eliminate inhomogeneities and air bubbles. Since cellulose ether provides a continuous viscoelastic skeleton and xanthan gum strengthens low shear yield stress and imparts shear dilution and structural recovery capabilities, the structural phase gradually encapsulates the stabilized particles during the formation process without destroying the network topology. This results in the network supporting the particles when standing, the viscosity decreasing and restoring flow when tilted or gently shaken, and maintaining uniformity and stability even after long-term use. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating a method for preparing a selenium disulfide detergent to improve its suspension stability, as proposed in this application. Figure 2 This is a schematic diagram of the static settlement test results of this application; Figure 3 This is a schematic diagram of the antioxidant stability test results for this application; Figure 4 This is a schematic diagram of the shear recovery rate test results of this application. Detailed Implementation

[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.

[0031] Related technologies rely on thickeners to increase the viscosity of the system, which can temporarily delay sedimentation, but often leads to loss of system fluidity and the formation of dense, hard precipitates after standing, making redispersible. While refining the particle size can reduce the sedimentation rate of individual particles, it cannot suppress secondary agglomeration and flocculation between fine particles, and stratification and uneven content will still occur in the later stages of storage. Furthermore, if there is a lack of synergistic control against oxidation and discoloration while thickening, oxidation products will change the surface properties of particles and further aggravate agglomeration and sedimentation, making it difficult to simultaneously achieve sedimentation inhibition, content uniformity, and flow recovery performance.

[0032] This application employs a sugar alcohol and chelating agent to pre-construct an antioxidant continuous phase, followed by pre-dispersion and wet dispersion of selenium disulfide to form a narrow particle size dispersed phase. This phase is then mixed with a structural phase composed of cellulose ether and xanthan gum. The sugar alcohol simultaneously increases the density and viscosity of the continuous phase and reduces the effective density difference between the particles and the continuous phase. The chelating agent reduces the catalytic effect of metal ions on the oxidation of the particle surface. The cellulose ether and xanthan gum form a shear-recoverable weak gel network. This results in a selenium disulfide detergent that settles slowly, is not prone to stratification, has a uniform content, and can recover its flowability under long-term static conditions.

[0033] Example 1: This example provides a method for preparing a detergent with improved suspension stability, comprising the following steps: S1. Mix and dissolve purified water, sugar alcohol and chelating agent to obtain an antioxidant continuous phase; The sugar alcohol used is glycerol, and the amount used is 2% of the total mass of selenium disulfide detergent; the chelating agent used is disodium ethylenediaminetetraacetate, and the amount used is 0.05% of the total mass of selenium disulfide detergent; the mixing and dissolving temperature is 20℃, the stirring rate is 100r / min, and the time is 30min.

[0034] S2. Selenium disulfide raw material is added to the antioxidant continuous phase for pre-dispersion to obtain selenium disulfide premix; The selenium disulfide raw material is pretreated before mixing: the selenium disulfide raw material is dried at low temperature under nitrogen protection at a temperature of 30°C and a vacuum of -0.08MPa for 4 hours, so that the moisture content is not higher than 0.5%; then it is sieved with a sieve mesh of 400 mesh, and the sieve material is collected as the selenium disulfide raw material used in this embodiment.

[0035] S3. Add a wetting and dispersing agent to the selenium disulfide premix and perform wet dispersion treatment to obtain a narrow particle size selenium disulfide dispersed phase. The wetting and dispersing agent used was polyoxyethylene sorbitan monooleate, with an amount of 0.1% of the total mass of the selenium disulfide detergent. The wet dispersion adopted a rotor-stator dispersion method with a dispersion rate of 2000 r / min and a time of 20 min. The system temperature did not exceed 30℃ during the process. The dispersion was stopped after the D50 reached 3 μm and the D90 was no greater than 15 μm. Then, a reducing protective agent was added, which was sodium metabisulfite, with an amount of 0.05% of the total mass of the selenium disulfide detergent. Citric acid was then added to adjust the pH of the system to 3.0 to obtain an antioxidant narrow particle size selenium disulfide dispersion phase.

[0036] S4. Cellulose ether and xanthan gum are separately dispersed in an aqueous phase containing glycerol, and then mixed after swelling and hydration treatment to obtain the structural phase; The xanthan gum content was 0.05% of the total mass of the selenium disulfide detergent, and the mass ratio of cellulose ether to xanthan gum was 10:1, i.e., the cellulose ether content was 0.50%. The swelling and hydration temperature of the cellulose ether was 20℃, and the time was 60 min. The dispersion temperature of xanthan gum was 20℃, the dispersion rate was 500 r / min, and the time was 30 min. The mass ratio of glycerol to xanthan gum in the structural phase was 20:1.

[0037] S5. Mix the narrow-particle-size selenium disulfide dispersed phase with the structural phase, and perform dispersion and homogenization treatment to obtain the initial product of selenium disulfide detergent. Before mixing, a surfactant, sodium dodecyl sulfate, is added to the narrow-particle-size selenium disulfide dispersed phase at a dosage of 0.5% of the total mass of the selenium disulfide detergent. During mixing, the structural phase is slowly added to the dispersed phase at a stirring rate of 1000 r / min for 30 min, followed by stirring at 1000 r / min for another 30 min. The homogenization process is carried out at a pressure of 5 MPa, with 3 cycles, and the system temperature does not exceed 35℃ during the homogenization process.

[0038] S6. Allow the initial selenium disulfide detergent to stand and balance to obtain a selenium disulfide detergent with improved suspension stability. The static equilibration was carried out under light-protected conditions at 20°C for 24 hours. After static equilibration, gentle redispersibility was performed by flipping the object 20 times at a flipping rate of 5 r / min for 5 min.

[0039] Based on the total mass of the selenium disulfide detergent, the selenium disulfide content is 2.5% w / w, the external phase pH is 3.0, and the remainder is pure water.

[0040] Example 2: This example provides a method for preparing a detergent with improved suspension stability, comprising the following steps: S1. Mix and dissolve purified water, sugar alcohol and chelating agent to obtain an antioxidant continuous phase; The sugar alcohol used is sucrose, and the amount used is 4% of the total mass of the selenium disulfide detergent; the chelating agent used is sodium citrate, and the amount used is 0.10% of the total mass of the selenium disulfide detergent; the mixing and dissolving temperature is 25℃, the stirring speed is 200r / min, and the time is 20min.

[0041] S2. Selenium disulfide raw material is added to the antioxidant continuous phase for pre-dispersion to obtain selenium disulfide premix; The selenium disulfide raw material is pretreated before mixing: the selenium disulfide raw material is dried at low temperature under nitrogen protection at a temperature of 35°C and a vacuum of -0.09MPa for 3 hours, so that the moisture content is not higher than 0.5%; then it is sieved with a sieve mesh of 300 mesh, and the sieve material is collected as the selenium disulfide raw material used in this embodiment.

[0042] S3. Add a wetting and dispersing agent to the selenium disulfide premix and perform wet dispersion treatment to obtain a narrow particle size selenium disulfide dispersed phase. The wetting and dispersing agent used was cocamidopropyl betaine, with an amount of 0.45% of the total mass of the selenium disulfide detergent. The wet dispersion was carried out using a rotor-stator dispersion method with a dispersion rate of 3500 r / min and a time of 12 min. The system temperature did not exceed 30℃ during the process. Dispersion was stopped after the D50 reached 5 μm and the D90 was no greater than 15 μm. Then, a reducing protectant was added, and ascorbic acid was selected as the reducing protectant, with an amount of 0.18% of the total mass of the selenium disulfide detergent. Sodium citrate was then added to adjust the pH of the system to 3.5, resulting in an antioxidant narrow particle size selenium disulfide dispersion phase.

[0043] S4. Cellulose ether and xanthan gum are separately dispersed in an aqueous phase containing glycerol, and then mixed after swelling and hydration treatment to obtain the structural phase; The xanthan gum content was 0.10% of the total mass of the selenium disulfide detergent, and the mass ratio of cellulose ether to xanthan gum was 6:1, i.e., the cellulose ether content was 0.60%. The swelling and hydration temperature of the cellulose ether was 25℃, and the time was 45 min. The dispersion temperature of xanthan gum was 25℃, the dispersion rate was 1000 r / min, and the time was 20 min. The mass ratio of glycerol to xanthan gum in the structural phase was 10:1.

[0044] S5. Mix the narrow-particle-size selenium disulfide dispersed phase with the structural phase, and perform dispersion and homogenization treatment to obtain the initial product of selenium disulfide detergent. Before mixing, a surfactant is added to the narrow-particle-size selenium disulfide dispersed phase. The surfactant is sodium lauroyl sarcosinate, and the amount used is 1.8% of the total mass of the selenium disulfide detergent. During mixing, the structural phase is first slowly added to the dispersed phase at a stirring rate of 1750 r / min for 20 min, and then stirring is continued at 1750 r / min for another 20 min. The homogenization pressure is 12 MPa, the number of cycles is 2, and the system temperature does not exceed 35℃ during the homogenization process.

[0045] S6. Allow the initial selenium disulfide detergent to stand and balance to obtain a selenium disulfide detergent with improved suspension stability. The static equilibration was carried out under light-protected conditions at 23°C for 18 hours. After static equilibration, gentle redispersibility was performed by flipping the container 13 times at a flipping rate of 13 r / min for a total flipping time of 3 min.

[0046] Based on the total mass of the selenium disulfide detergent, the selenium disulfide content is 2.5% w / w, the external phase pH is 3.5, and the remainder is pure water.

[0047] Example 3: This example provides a method for preparing a selenium disulfide detergent with improved suspension stability, comprising the following steps: S1. Mix and dissolve purified water, sugar alcohol and chelating agent to obtain an antioxidant continuous phase; The sugar alcohol used is sorbitol, which accounts for 6% of the total mass of the selenium disulfide detergent; the chelating agent used is sodium phytate, which accounts for 0.15% of the total mass of the selenium disulfide detergent; the mixing and dissolving temperature is 30℃, the stirring rate is 300r / min, and the time is 10min.

[0048] S2. Selenium disulfide raw material is added to the antioxidant continuous phase for pre-dispersion to obtain selenium disulfide premix; The selenium disulfide raw material is pretreated before mixing: the selenium disulfide raw material is dried at low temperature under nitrogen protection at a temperature of 40°C and a vacuum of -0.10 MPa for 2 hours, so that the moisture content is not higher than 0.5%; then it is sieved with a sieve mesh of 200 mesh, and the sieve material is collected as the selenium disulfide raw material used in this embodiment.

[0049] S3. Add a wetting and dispersing agent to the selenium disulfide premix and perform wet dispersion treatment to obtain a narrow particle size selenium disulfide dispersed phase. The wetting and dispersing agent used was polyoxyethylene sorbitan monolaurate, with an amount of 0.8% of the total mass of the selenium disulfide detergent. The wet dispersion adopted a rotor-stator dispersion method with a dispersion rate of 5000 r / min and a time of 5 min. The system temperature did not exceed 30℃ during the process. The dispersion was stopped after the D50 reached 8 μm and the D90 was no greater than 15 μm. Then, a reducing protectant was added, which was sodium bisulfite, with an amount of 0.30% of the total mass of the selenium disulfide detergent. Citric acid was then added to adjust the pH of the system to 4.0 to obtain an antioxidant narrow particle size selenium disulfide dispersion phase.

[0050] S4. Cellulose ether and xanthan gum are separately dispersed in an aqueous phase containing glycerol, and then mixed after swelling and hydration treatment to obtain the structural phase; The xanthan gum content was 0.17% of the total mass of the selenium disulfide detergent, and the mass ratio of cellulose ether to xanthan gum was 4:1, i.e., the cellulose ether content was 0.68%. The swelling and hydration temperature of the cellulose ether was 30℃, and the time was 30 min. The dispersion temperature of xanthan gum was 30℃, the dispersion rate was 1500 r / min, and the time was 10 min. The mass ratio of glycerol to xanthan gum in the structural phase was 5:1.

[0051] S5. Mix the narrow-particle-size selenium disulfide dispersed phase with the structural phase, and perform dispersion and homogenization treatment to obtain the initial product of selenium disulfide detergent. Before mixing, a surfactant is added to the narrow-particle-size selenium disulfide dispersed phase. The surfactant used is cocamidopropyl betaine, and the amount used is 3.0% of the total mass of the selenium disulfide detergent. During mixing, the structural phase is first slowly added to the dispersed phase at a stirring rate of 2500 r / min for 10 min, and then stirring is continued at 2500 r / min for 10 min. The homogenization pressure is 20 MPa, the number of cycles is 1, and the system temperature does not exceed 35℃ during the homogenization process.

[0052] S6. Allow the initial selenium disulfide detergent to stand and balance to obtain a selenium disulfide detergent with improved suspension stability. The static equilibration was carried out under light-protected conditions at 25°C for 12 hours. After static equilibration, gentle redispersibility was performed by flipping the object 5 times at a flipping rate of 20 r / min for 1 minute.

[0053] Based on the total mass of the selenium disulfide detergent, the selenium disulfide content is 2.5% w / w, the external phase pH is 4.0, and the remainder is pure water.

[0054] Comparative Example 1: This comparative example refers to the content of Example 1, except that sugar alcohol is not added in S1 and the amount of purified water is supplemented, that is, the density and viscosity of the continuous phase are not increased by sugar alcohol. The rest of the content is the same as that of Example 1.

[0055] Comparative Example 2: This comparative example is based on the content of Example 1, except that no chelating agent is added in S1 and the amount of purified water is supplemented, that is, disodium ethylenediaminetetraacetate is not present in the antioxidant continuous phase. The rest of the content is the same as that of Example 1.

[0056] Comparative Example 3: This comparative example refers to the content of Example 1, except that the low-temperature drying and sieving pretreatment before S2 are not performed. Instead, the undried selenium disulfide raw material is directly added to the antioxidant continuous phase. The rest of the content is the same as that of Example 1.

[0057] Comparative Example 4: This comparative example refers to the content of Example 1, except that no wetting and dispersing agent is added in S3, the amount of purified water is replenished, and the wet dispersion is stopped before the particle size distribution of D50 is 3μm to 8μm and D90 is not greater than 15μm, so that the particle size distribution of selenium disulfide particles is wider. The rest is the same as Example 1.

[0058] Comparative Example 5: This comparative example refers to the content of Example 1, except that only cellulose ether is used in the structure phase of S4, and xanthan gum is not added, that is, a weak gel network of cellulose ether and xanthan gum synergistically is not formed. The rest of the content is the same as that of Example 1.

[0059] Comparative Example 6: This comparative example refers to the content of Example 1, except that after S3, the antioxidant protection step of adding a reducing agent and adjusting the pH with citric acid is not performed, that is, the antioxidant boundary of chelation, reduction and acidic environment synergy is not formed. The rest of the content is the same as Example 1.

[0060] Performance testing Sample preparation: After the samples of Examples 1 to 3 and Comparative Examples 1 to 6 were prepared according to the corresponding steps, they were allowed to stand and equilibrate for a specified time in a light-proof environment at 25°C. The upper, middle and lower layers of each sample were then placed into stoppered glass bottles, sealed, and stored at 40°C and 75% relative humidity for 3 months. Samples were taken every 15 days for various performance tests. The sampling, testing environment and instrument conditions of all samples were kept consistent. Before the test, the samples were flipped 10 times at a flipping speed of 5r / min to 20r / min to remix them evenly, so as to avoid errors introduced by human operation differences during the test.

[0061] Static sedimentation and stratification stability testing: After static equilibration, each sample was placed vertically in a graduated test tube and stored at 25°C for 3 months. The height of the stratification interface between the supernatant and the dispersed phase, as well as the volume of the bottom precipitate, were recorded periodically. The stratification rate was calculated as the ratio of the stratification interface height to the total sample height, and the bottom precipitate volume was calculated as the ratio of the precipitate volume to the total sample volume. After storage, the presence of hard precipitate at the bottom was observed, and the redispersion after gentle shaking was evaluated to assess the effect of sugar alcohol density matching and weak gel network on sedimentation and stratification inhibition. Test standards: The stratification rate and precipitate volume were determined using a combination of static stratification and visual inspection, following the general methods for testing the storage stability of dispersion systems. Centrifugation acceleration conditions were based on the ASTM D4212 centrifugal sedimentation method. The sedimentation particle size standard was determined according to GB / T19077 "Particle size distribution - Laser diffraction method".

[0062] Selenium disulfide content uniformity test: After 3 months of storage, the upper, middle, and lower layers of each sample were taken. Following the content determination method under the "Selenium Disulfide Lotion" section of the Chinese Pharmacopoeia, the samples were nitrated with fuming nitric acid and titrated with sodium thiosulfate solution. The endpoint was determined using potassium iodide-starch indicator. The selenium disulfide content of each layer was calculated, and the relative standard deviation of the three layers was used as the content uniformity index. Simultaneously, the content retention rate before and after storage was calculated to evaluate the effect of narrow particle size dispersion and weak gel network on maintaining the uniformity of selenium disulfide distribution and dosage consistency. Test standards: The selenium disulfide content determination was performed according to the "Selenium Disulfide Lotion" section of the Chinese Pharmacopoeia, using the titration method according to General Rule 0701; the content uniformity evaluation referred to the "Content Uniformity Inspection Method" in General Rule 0941 of Part IV of the Chinese Pharmacopoeia.

[0063] Antioxidant and color difference stability testing: Color difference was measured using a colorimeter before and after 3 months of storage for each sample. Simultaneously, the oxidation degree of selenium disulfide in the samples was determined according to the method described in the Chinese Pharmacopoeia under the selenium disulfide section. The increase in color difference and oxidation degree over time was used to evaluate the synergistic antioxidant boundary effect of the chelating agent, reducing protectant, and acidic buffer system on inhibiting discoloration and surface oxidation. Testing standards: Color difference measurement and calculation were performed according to GB / T3979 "Methods for Measurement of Object Color" and GB / T7921 "Uniform Color Space and Color Difference Formula"; the determination of selenium disulfide content and oxidation degree was performed according to the method described in the selenium disulfide section of the Chinese Pharmacopoeia.

[0064] Rheological properties and shear recovery testing: Rheological tests were performed on each sample using a rotational rheometer. First, the viscosity change curve was measured at 25℃ as the shear rate increased from low to high and then returned to a low value. The viscosity and yield stress at the low shear rate were recorded. Then, the viscosity was measured by pre-shearing at a fixed low shear rate for a certain period of time, followed immediately by switching to a high shear rate. After shearing stopped, the viscosity recovery curve was measured at the same low shear rate. The shear recovery rate, i.e., the ratio of recovered viscosity to initial viscosity, was used to evaluate the effect of the cellulose ether and xanthan gum weak gel network on particle support and flow recovery. Test standards: Viscosity and rheological properties were determined according to the rotational method of GB / T10247 "Methods for Measurement of Viscosity"; the shear rate scan, yield stress, and thixotropic ring determination conditions were in accordance with ISO3219 "Determination of viscosity of liquid or emulsion polymer dispersions in plastics using a rotational viscometer".

[0065] Table 1: Results of static settlement and stratification stability tests ; Table 2: Results of content uniformity and antioxidant stability tests ; Table 3: Results of Rheological Properties and Shear Recovery Tests ; Example Conclusion: See appendix Figure 1 - Appendix Figure 4 Based on the technical solutions of Examples 1-3 and Comparative Examples 1-6, the following conclusions are drawn: Combining Examples 1-3 and Comparative Example 1 with Table 1, it can be seen that sugar alcohols have an impact on the sedimentation and stratification inhibition of selenium disulfide detergent. In Comparative Example 1, without the addition of sugar alcohol, the stratification rate and sedimentation volume increased significantly, and hard sediment appeared, requiring a significant increase in the number of turnings required for redispersion. In contrast, Examples 1-3 maintained a state without hard sediment and easy redispersion. This indicates that sugar alcohols weaken the driving force of gravity sedimentation by simultaneously increasing the density and viscosity of the continuous phase and reducing the effective density difference between selenium disulfide particles and the continuous phase. When sugar alcohol is absent, even with a weak gel network, the density difference between the particles and the continuous phase will still cause the particles to continue to settle and gradually accumulate to form a hard sediment during the standing process. Thus, it can be seen that the density matching and viscosity regulation effects of sugar alcohols and the supporting effect of the weak gel network complement each other, and only through their synergy can slow sedimentation, non-stratification, and no hard sediment at the bottom be achieved simultaneously.

[0066] Combining Examples 1-3 and Comparative Example 2 with Table 2, it can be seen that the chelating agent is the key to inhibiting the oxidative discoloration of selenium disulfide. In Comparative Example 2, without the addition of a chelating agent, the color difference and degree of oxidation were significantly increased compared to the examples, and the content retention rate decreased, while Examples 1-3 maintained a low color difference and degree of oxidation. This indicates that the chelating agent preferentially binds to free metal ions in the system, blocking the path of metal ion-catalyzed oxidation, thus maintaining the surface of selenium disulfide particles in a relatively stable reduced state. When the chelating agent is absent, trace metal ions will continue to catalyze surface oxidation, leading to darker color, changes in particle surface properties, and further inducing aggregation, ultimately affecting dispersion stability. Therefore, the chelating agent, reducing agent, and acidic buffer system together constitute the antioxidant boundary, and the synergistic effect of the three is necessary to persistently inhibit discoloration and secondary aggregation.

[0067] Combining Examples 1-3 and Comparative Example 3 with Table 2, it can be seen that the inert atmosphere low-temperature drying and sieving pretreatment of the raw materials have an impact on long-term dispersion stability. In Comparative Example 3, without pretreatment, the content uniformity deteriorates and the degree of oxidation increases, while the content distribution in the upper, middle, and lower layers of Examples 1-3 is more consistent. This indicates that pretreatment, by removing adsorbed moisture from the surface of the raw materials and removing agglomerated large particles and mechanical impurities, makes the initial particle size distribution of selenium disulfide raw materials narrower, the surface cleaner, and has suitable activity, thus making it easier for them to be uniformly coated by wetting and dispersing agents in the subsequent wetting and dispersion process. When pretreatment is missing, moisture and large particle agglomerates in the raw materials will be introduced into the dispersion system, disrupting the viscosity and pH balance of the continuous phase and increasing the risk of secondary agglomeration. Therefore, pretreatment provides a clean and uniform basis for narrow particle size dispersion and the establishment of antioxidant boundaries.

[0068] Combining Examples 1-3 and Comparative Example 4 with Tables 1 and 2, it can be seen that the directional adsorption of the wetting and dispersing agent and the control of narrow particle size distribution play a role in the uniformity of content. In Comparative Example 4, without the addition of a wetting and dispersing agent and with a wide particle size distribution, the stratification rate, sedimentation volume, and content difference between upper and lower layers all increased significantly, and hard sedimentation occurred. In contrast, the particle distribution in Examples 1-3 was uniform, and there was no hard sedimentation at the bottom. This indicates that after the wetting and dispersing agent forms a steric hindrance layer on the particle surface, it can inhibit bridging flocculation between particles and agglomeration caused by van der Waals attraction. Combined with the narrow particle size control of timely stopping grinding, it makes it difficult for particles of different sizes to settle individually or form sedimentation chains. When the wetting and dispersing agent is missing and the particle size distribution is too wide, large particles settle quickly, and fine particles are prone to flocculation. Both of these factors exacerbate stratification and content unevenness. Therefore, it can be seen that steric hindrance and narrow particle size distribution have a synergistic effect in inhibiting sedimentation and ensuring dosage consistency.

[0069] Combining Examples 1-3 and Comparative Example 5 with Tables 1 and 3, it can be seen that the dual-polymer weak gel network composed of cellulose ether and xanthan gum is the influencing factor that balances suspension stability and flow recovery. In Comparative Example 5, when a single polymer is used without xanthan gum, the viscosity and yield stress are relatively high, but the stratification and sedimentation are still obvious and the shear recovery rate is reduced. In contrast, Examples 1-3 all showed the ability to support the particles after standing and to recover flow after shearing. This indicates that cellulose ether mainly provides a continuous viscoelastic skeleton to maintain the yield stress, while xanthan gum strengthens the low shear yield stress with a lower dosage and endows the system with shear dilution and structural recovery properties. The two work together in a specific ratio to form a recoverable weak gel rather than a permanently rigid gel. When only a single polymer is used, the system either has too high a viscosity, leading to flow difficulties, or the network lacks recovery ability and forms sedimentation channels after standing. It can be seen that there is a balance between supporting particles and maintaining flow recoverability in the dual-polymer network.

[0070] Combining Examples 1-3 and Comparative Example 6 with Table 2, it can be seen that the antioxidant protection step consisting of the reducing agent and the acidic buffer system has an impact on inhibiting discoloration. Comparative Example 6 showed the worst color difference and oxidation degree among all groups when the antioxidant protection step was not performed, while Examples 1-3 maintained a low oxidation level. This indicates that the reducing agent can preferentially consume dissolved oxygen and initial oxidation products in the system, maintaining the surface of selenium disulfide particles in a reduced state, while the acidic environment further inhibits the catalytic activity of metal ions. The two, together with the chelating agent, form a triple synergistic antioxidant boundary. When this protective step is missing, the oxidation of the particle surface will gradually change its surface charge and adsorption behavior, thereby destroying the compatibility between the dispersion layer and the polymer network.

[0071] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing a detergent with improved suspension stability, characterized in that, Includes the following steps: S1. Mix and dissolve purified water, sugar alcohol and chelating agent to obtain an antioxidant continuous phase; S2. Selenium disulfide raw material is added to the antioxidant continuous phase for pre-dispersion to obtain selenium disulfide premix; S3. Add a wetting and dispersing agent to the selenium disulfide premix and perform wet dispersion treatment to obtain a narrow particle size selenium disulfide dispersed phase. S4. Cellulose ether and xanthan gum are separately dispersed in an aqueous phase containing glycerol, and then mixed after swelling and hydration treatment to obtain the structural phase; S5. Mix the narrow-particle-size selenium disulfide dispersed phase with the structural phase, and perform dispersion and homogenization treatment to obtain the initial product of selenium disulfide detergent. S6. The initial product of selenium disulfide detergent is allowed to stand and balance to obtain a selenium disulfide detergent with improved suspension stability. Based on the total mass of the selenium disulfide detergent, the selenium disulfide content is 2.5% w / w, the sugar alcohol content is 2% to 6%, the chelating agent content is 0.05% to 0.15%, the cellulose ether content is 0.30% to 0.70%, the xanthan gum content is 0.05% to 0.20%, the mass ratio of the cellulose ether to the xanthan gum is 4:1 to 10:1, the external phase pH of the detergent is 3.0 to 4.0, and the balance is pure water.

2. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S1, the sugar alcohol is one or more of glycerol, sucrose, or sorbitol; the chelating agent is one or more of disodium ethylenediaminetetraacetate, sodium citrate, or sodium phytate; the mixing and dissolving temperature is 20°C to 30°C, the stirring rate is 100 r / min to 300 r / min, and the time is 10 min to 30 min.

3. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, Before step S2, the selenium disulfide raw material is pretreated: the selenium disulfide raw material is dried at low temperature under an inert atmosphere, with a drying temperature of 30°C to 40°C, a vacuum degree of -0.08MPa to -0.10MPa, and a time of 2h to 4h; then the dried selenium disulfide raw material is sieved with a sieve mesh of 200 to 400 mesh, and the undersize material is collected as the selenium disulfide raw material used in step S2.

4. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S3, the wetting and dispersing agent is one or more of polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monolaurate, or cocamidopropyl betaine; based on the total mass of the selenium disulfide detergent, the content of the wetting and dispersing agent is 0.1% to 0.8%; the wet dispersion treatment adopts a rotor-stator dispersion method, the dispersion rate is 2000 r / min to 5000 r / min, the time is 5 min to 20 min, and the system temperature does not exceed 30℃ during the treatment; the dispersion is stopped after D50 reaches 3 μm to 8 μm and D90 ≤ 15 μm.

5. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, The process after step S3 includes antioxidant protection: a reducing agent, which is one or more of sodium metabisulfite, sodium bisulfite, or ascorbic acid, is added to the narrow-particle-size selenium disulfide dispersion, with a content of 0.05% to 0.30%; then a citric acid or citrate buffer system is added to adjust the pH of the system to 3.0 to 4.0 to obtain an antioxidant narrow-particle-size selenium disulfide dispersion for mixing in step S5.

6. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S4, the mass ratio of cellulose ether to xanthan gum is 4:1 to 10:1; the swelling and hydration temperature of cellulose ether is 20°C to 30°C, and the time is 30 min to 60 min; the dispersion temperature of xanthan gum is 20°C to 30°C, the dispersion rate is 500 r / min to 1500 r / min, and the time is 10 min to 30 min; the mass ratio of glycerol to xanthan gum in the structural phase is 5:1 to 20:

1.

7. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S5, the mixing is as follows: the structural phase is slowly added to the narrow-particle-size selenium disulfide dispersion phase at a stirring rate of 1000 r / min to 2500 r / min for 10 min to 30 min, and then stirring is continued at 1000 r / min to 2500 r / min for 10 min to 30 min; the homogenization pressure of the homogenization treatment is 5 MPa to 20 MPa, the number of cycles is 1 to 3, and the system temperature does not exceed 35°C during the homogenization process.

8. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S5, before mixing the structural phase with the narrow-particle-size selenium disulfide dispersion, a surfactant is added to the narrow-particle-size selenium disulfide dispersion; the surfactant is one or more of sodium dodecyl sulfate, sodium lauroyl sarcosinate, or cocamidopropyl betaine, in a content of 0.5% to 3.0%.

9. The preparation method for improving the suspension stability of selenium disulfide detergent according to claim 1, characterized in that, In step S6, the static equilibration is to let the mixture stand at 20°C to 25°C for 12 to 24 hours under light-protected conditions.

10. The method for preparing a selenium disulfide detergent with improved suspension stability according to claim 1, characterized in that, In step S6, after the static equilibrium is completed, the selenium disulfide detergent is gently redispersed by turning it 5 to 20 times at a turning rate of 5 to 20 r / min for 1 to 5 min.